Maternally and Paternally Silenced Imprinted Genes Differ in Their Intron Content. Issue 8 (2004) - Fahey, Marie E.; Mills, Walter; Higgins, Desmond G.; Moore, Tom
Abstract : Imprinted genes exhibit silencing of one of the parental alleles during embryonic development. In a previous study imprinted genes were found to have reduced intron content relative to a non-imprinted control set (Hurst et al ., 1996). However, due to the small sample size, it was not possible to analyse the source of this effect. Here, we re-investigate this observation using larger datasets of imprinted and control (non-imprinted) genes that allow us to consider mouse and human, and maternally and paternally silenced, imprinted genes separately. We find that, in the human and mouse, there is reduced intron content in the maternally silenced imprinted genes relative to a non-imprinted control set. Among imprinted genes, a strong bias is also observed in the distribution of intronless genes, which are found exclusively in the maternally silenced dataset. The paternally silenced dataset in the human is not different to the control set; however, the mouse paternally silenced dataset has more introns than the control group. A direct comparison of mouse maternally and paternally silenced imprinted gene datasets shows that they differ significantly with respect to a variety of intron-related parameters. We discuss a variety of possible explanations for our observations.